Motivation to Learn English for Junior High School Students in Yogyakarta - Namira Prasetya Rizky Ramadhani; Rahmi Munfangati (Universitas Majalengka, 2023)
The aim of study was to analyze the level of motivation in junior high school students, especially in English lessons. This is because the average English test scores in junior high schools are still not stable above the KKM (minimum completeness criteria). This type of research is a quantitative descriptive. The method used in this study is a survey and data collection techniques using a questionnaire. The sample in this study was 335 students from 16 junior high schools in Yogyakarta City. The results of the research on the motivation to learn English for junior high school students in the city of Yogyakarta based on the intrinsic motivation of learning English for junior high school students in the city of Yogyakarta were in a